Islamic Rituals in Plural Societies: The Cultural and Religious Significance of Turun Kasunge in Sosorgadong - Hazri Sakinah Hutagalung; Dahlia Lubis (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2025)
This study examines the Turun Kasunge ritual as a unique expression of local Islamic practice within the multicultural society of Sosorgadong, North Sumatra. The ritual involves symbolic elements such as lime water, flour, and incense, each carrying specific meanings related to gratitude, purification, protection, and spiritual renewal. Although the tradition is practiced exclusively by the Muslim community, it is respected and accommodated by people of other faiths in the area, reflecting a culture of tolerance, coexistence, and mutual respect. Using a qualitative approach that includes in-depth interviews, participant observation, and documentation, the research explores how Islamic spiritual values are embedded and negotiated within local cultural frameworks. The findings reveal that Turun Kasunge not only reinforces religious identity but also promotes social cohesion and communal harmony. It serves as a living example of how religious rituals can contribute to the values of religious moderation, interfaith understanding, and peaceful pluralism in everyday life. This study contributes to broader discussions on local Islam, ritual symbolism, and the role of religious practices in maintaining social integration in diverse communities.